Adenoviruses in the immunocompromised host. - Hierholzer, J C (1992)
Adenoviruses are among the many pathogens and opportunistic agents that cause serious infection in the congenitally immunocompromised, in patients undergoing immunosuppressive treatment for organ and tissue transplants and for cancers, and in human immunodeficiency virus-infected patients. Adenovirus infections in these patients tend to become disseminated and severe, and the serotypes involved are clustered according to the age of the patient and the nature of the immunosuppression. Over 300 adenovirus infections in immunocompromised patients, with an overall case fatality rate of 48%, are reviewed in this paper. Children with severe combined immunodeficiency syndrome and other primary immunodeficiencies are exposed to the serotypes of subgroups B and C that commonly infect young children, and thus their infections are due to types 1 to 7 and 31 of subgenus A. Children with bone marrow and liver transplants often have lung and liver adenovirus infections that are due to an expanded set of subgenus A, B, C, and E serotypes. Adults with kidney transplants have viruses of subgenus B, mostly types 11, 34, and 35, which cause cystitis. This review indicates that 11% of transplant recipients become infected with adenoviruses, with case fatality rates from 60% for bone marrow transplant patients to 18% for renal transplant patients. Patients with AIDS become infected with a diversity of serotypes of all subgenera because their adult age and life-style expose them to many adenoviruses, possibly resulting in antigenically intermediate strains that are not found elsewhere. Interestingly, isolates from the urine of AIDS patients are generally of subgenus B and comprise types 11, 21, 34, 35, and intermediate strains of these types, whereas isolates from stool are of subgenus D and comprise many rare, new, and intermediate strains that are untypeable for practical purposes. It has been estimated that adenoviruses cause active infection in 12% of AIDS patients and that 45% of these infections terminate in death within 2 months. In all immunocompromised patients, generalized illness involving the central nervous system, respiratory system, hepatitis, and gastroenteritis usually have a fulminant course and result in death. Treatments for adenovirus infections are of little proven value, although certain purine and pyrimidine analogs have shown beneficial effects in vitro and may be promising drugs.